The 17th Polar Law Symposium and the Opening Speech of Rector Anders Fällström - Anders Fällström; Øyvind Ravna; Ekaterina Zmyvalova (Arctic Review on Law and Politics)
From September 23 to 26, 2024, Gaskeuniversiteete (Mid Sweden University) hosted the 17th Polar Law Symposium. The event was officially opened by the university’s rector, Anders Fällström, who, in his speech, underscored the significance of the symposium for both the university and its role as a global institution with a strong commitment to regional engagement. Fällström highlighted that Gaskeuniversiteete is the only university in Sweden located within the South Sámi region, with Sámi issues forming a central part of its academic mission.